Properties of strength and elasticity of structural elements of round timber of AMARU for use in civil construction - Icimoto, Felipe Hideyoshi; De Souza, Amós Magalhães; Fernandes, Caio Victor [UNESP]; Ferro, Fabiane Salles; Júnior, Carlito Calil (My University, 2014)
The use of timber structural elements in Brazil has grown over the past few years due to researches conducted in order to make it more competitive compared to other materials used in structural function, such as steel and concrete. Considering the need to find alternative economically-viable materials that meet the requirements of sustainable construction, the constructions with round timber, used in civil construction, rural buildings, bridges, pedestrian bridges, fendering and electricity transmission line poles appear as an option to this major challenge to reconcile aspects of social, economic and environmental. The strength of round timber, its low weight, low power consumption for processing, its availability and easiness in handling make it become a material highly competitive and sustainable. This study aims to determine the properties of strength and elasticity in bending, compression parallel to grain, tension parallel to grain, shear, moisture and density in round timber structural elements of the clone of Eucalyptus called AMARU developed by a Brazilian company, based in the recent review of the Brazilian Standard of the timber in force NBR7190/1997 - Design of timber structures - that proposes the methodology of mechanical tests of structural elements. The values obtained are the basis for engineers and architects to design structures using AMARU wood specie.
Keywords: Eucalyptus AMARU species; Eucalyptus sp; Mechanical properties; Reforestation species; Round timber